An Open‐Label, Randomized, 2‐Way, Crossover Bioequivalence Study of Cefradine Capsules in Healthy Chinese Volunteers. Issue 12 (20th June 2021) - Lai, Xiuping; Ye, Suiwen; Chen, Liuhan; Chen, Junyi; Zhang, Nan; Zhang, Yiwen; Wu, Junyan; Yao, Herui
Abstract: The purpose of this study was to evaluate whether test cefradine capsules and reference cefradine capsules were bioequivalent in healthy Chinese volunteers. An open‐label, randomized, biperiodic, crossover design was used. In each of the 2 study periods (separated by a 1‐week washout period), 250‐mg single doses of either the test or reference cefradine capsule were administered to study participants under fasted and fed conditions. Blood samples were collected at intervals from predose to 8 hours afterward. In the fasting study, the 90% confidence intervals (90%CI) of the Cmax, AUC0‐8h, and AUC0‐∞ for the test and reference preparations were 93.7%‐112.2%, 94.6%‐100.8%, and 94.7%‐100.9%, respectively. In the fed study, the 90%CI of the Cmax, AUC0‐8h, and AUC0‐∞ for the test and reference preparations was 81.0%‐99.1%, 100.5%‐106.3%, and 100.5%‐105.9%, respectively. The results showed that the test cefradine capsules and the reference formulation are bioequivalent under both fasting and fed conditions.